The Relationship between PBLS and Osteosarcoma Distribution in Different Subgroups and the Survival and Prognosis of Osteosarcoma. (7th April 2023) - Luo, Peng; Zhou, Peng
Abstract : Objective . To analyze the differences in the distribution of lymphocytes (PBLS) in different subgroups of osteosarcoma (OS) and the predictive value of related parameters on the survival prognosis of OS. Methods . For retrospective analysis, 80 patients with malignant OS diagnosed and treated in our hospital from June 2016 to June 2017 were selected as the observation group, and 80 patients with benign bone tumors during the same period were selected as the control group. Patients in the observation group were followed up for three years and grouped according to the tumor diameter, stage, metastasis, and prognosis. Fasting venous blood was collected from each group and the levels of CD3+, CD3+CD4+, and CD3+CD8+ were detected. Meanwhile, the ratio of CD4+/CD8+, CD4+/CD3+, and CD8+/CD3+ was calculated and compared. Kaplan–Meier survival curve was used to analyze the relationship between PBLS parameters and OS survival. The area under the curve (AUC), sensitivity, and specificity of each entry index were analyzed by the receiver operating characteristic curve (ROC curve). Results . The CD3+CD8+ level and CD4+/CD3+ ratio in the observation group were significantly higher than those in the control group (P < 0.05 ). The level of CD3+CD8+ in the patients with tumor diameter ≥ 11 cm was observably higher than that in the patients with tumor diameter <11 cm (P < 0.05 ). The levels of CD3+CD4+ and the ratio of CD4+/CD8 and CD4+/CD3+ of patients in stage III were markedly lower than those of patients in stage II, while the ratio of CD8+/CD3+ and the levels of CD3+CD8+ were prominently higher than those of patients in stage II (P < 0.05 ). The CD3+CD4+ level and CD4+/CD3+ ratio of patients in the metastatic group before treatment, the metastatic group after treatment, and the nonmetastatic group after treatment increased successively, while the ratio of CD4+/CD8+ and CD8+/CD3+ and the level of CD3+CD8+ decreased successively (P < 0.05 ). The CD3+CD4+ level and CD4+/CD3+ ratio in the poor prognosis group were significantly higher than those in the good prognosis group, whereas the ratio of CD8+/CD3+ and CD4+/CD8+ and the level of CD3+CD8+ were significantly lower than those in the poor prognosis group (P < 0.05 ). ROC curve analysis showed that the AUC of CD4+/CD8+ and CD4+/CD3+ in predicting poor prognosis in patients with OS was notably higher than other indicators, which were 0.818 and 0.866, respectively (P < 0.05 ). Kaplan–Meier survival curve results revealed that patients with CD3+CD4+ ≤ 5.15, CD3+CD8+ > 3.85, CD4+/CD8+ ≤ 1.42, CD4+/CD3+ ≤ 0.50, and CD8+/CD3+ > 0.38 had longer survival. Conclusion . The distribution of PBLS parameters varied widely among different subgroups of OS. Patients with poor prognosis had a higher ratio of CD4+/CD8+ and CD4+/CD3+, which were related to the survival of patients with OS. Moreover, both the ratio of CD4+/CD8+ and CD4+/CD3+ had certain predictive values in terms of survival and prognosis of OS. Therefore, regular clinical monitoring of patients' immune function could help predict disease changes and assess prognosis.